MinJoin++: a fast algorithm for string similarity joins under edit distance - Karpov, Nikolai; Zhang, Haoyu; Zhang, Qin (The VLDB journal, 2024)
We study the problem of computing similarity joins under edit distance on a set of strings. Edit similarity joins is a fundamental problem in databases, data mining and bioinformatics. It finds many applications in data cleaning and integration, collaborative filtering, genome sequence assembly, etc. This problem has attracted a lot of attention in the past two decades. However, all previous algorithms either cannot scale to long strings and large similarity thresholds, or suffer from imperfect accuracy. In this paper, we propose a new algorithm for edit similarity joins using a novel string partition-based approach. We show that, theoretically, our algorithm finds all similar pairs with high probability and runs in linear time (plus a data-dependent verification step). The algorithm can also be easily parallelized. Experiments on real-world datasets show that our algorithm outperforms the state-of-the-art algorithms for edit similarity joins by orders of magnitudes in running time and achieves perfect accuracy on most datasets that we have tested.